1990
DOI: 10.1080/00343409012331345754
|View full text |Cite
|
Sign up to set email alerts
|

Searching for New Manufacturing Plant Locations: A Study of Location Decisions in Central Appalachia

Abstract: A la recherche de nouveaux emplacements: une ttude en Appalachia central des decisions portant sur la localisation, Reg. Studies 23, 15-30. Cet article analyse le comportement des fabricants en Appalachia central i la recherche d'un emplacement, et developpe un mod& de la prise de decisions hitrarchique sous des conditions d'informations imparfaites. Des interviews des managers des ttablissements permettent une tvaluation des faqons locales et rtgionales de faire de la recherche. I1 est demontrt que l'ensemble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…New establishments are choosing manufacturing locations based on site characteristics that affect their profitability .9 If these factors are correlated with the discriminatory variables included in the previous model, then the results may be substantially different. Six variables were selected which have been used in the industrial location literature (Walker and Calzonetti 1989;Wheeler and Muller 1986).…”
Section: Tobit Analysis Of Toxic Releasesmentioning
confidence: 99%
“…New establishments are choosing manufacturing locations based on site characteristics that affect their profitability .9 If these factors are correlated with the discriminatory variables included in the previous model, then the results may be substantially different. Six variables were selected which have been used in the industrial location literature (Walker and Calzonetti 1989;Wheeler and Muller 1986).…”
Section: Tobit Analysis Of Toxic Releasesmentioning
confidence: 99%
“…A study by Walker and Calzonetti (1990) found that multiple location firms or selection of branch locations is driven more by cost considerations, while criteria for single locations are less clear. Results suggested that large energy-intensive branch manufacturing plants examine energy and transportation costs.…”
Section: Studies Of Manufacturing Site Locationmentioning
confidence: 99%
“…Because of these human limitations and in order to represent choices in a manageable way, it has been proposed that migration decisions be modeled in a nested, hierarchical manner (Holm and Malmberg 1997;Moore and Rosenberg 1995). A similar hierarchical approach has been recommended to represent industrial location search by firms (Walker and Calzonetti 1990).…”
Section: Decomposing the Migration Decisionmentioning
confidence: 99%